Understanding the Factors Influencing Repeat Visits Among Solaria Customers: A Behavioral Analysis - Rahmawati, Anita; Istia, Maria Nino; Bakri, M. Jamal Al (Dinasti Publisher, 2024)
This study aims to understand the factors influencing repeat visits among customers of Solaria, a popular Indonesian restaurant chain. Utilizing a quantitative approach, the research involved a survey of 200 respondents who had dined at Solaria more than once. The findings reveal that food quality, service quality, price perception, and restaurant atmosphere significantly impact customers' decisions to return. These insights provide valuable implications for Solaria's management in enhancing customer loyalty and improving marketing strategies.